27‐gauge microincision vitrectomy surgery compared with 25‐gauge microincision vitrectomy surgery on wound closure and need for wound suture and other postoperative parameters in the treatment of vitreoretinal disease: A meta‐analysis. Issue 3 (4th August 2022) - Li, Siying; Li, Yichun; Wei, Lulu; Fang, Fang; Jiang, Yulan; Chen, Keyan; Yang, Xiaotian; Liu, Hongwei
Abstract: We performed a meta‐analysis to evaluate the effect of 27‐gauge microincision vitrectomy surgery compared with 25‐gauge microincision vitrectomy surgery on wound closure and the need for wound suture and other postoperative parameters in the treatment of vitreoretinal disease. A systematic literature search up to June 2022 was performed and 1264 subjects with the vitreoretinal disease at the baseline of the studies; 562 of them were using the 27‐gauge microincision vitrectomy surgery, and 722 were using 25‐gauge microincision vitrectomy surgery. Odds ratio (OR), and mean difference (MD) with 95% confidence intervals (CIs) were calculated to assess the effect of 27‐gauge microincision vitrectomy surgery compared with 25‐gauge microincision vitrectomy surgery on wound closure and the need for wound suture and other postoperative parameters in the treatment of vitreoretinal disease using the dichotomous, and contentious methods with a random or fixed‐effect model. The 27‐gauge microincision vitrectomy surgery subjects had a significantly lower intraoperative and postoperative wound complication (OR, 6.66; 95% CI, 0.46‐0.95, P  = .02), and wound suture number (OR, 0.38; 95% CI, 0.20‐0.71, P  = .002), and best corrected visual acuity (MD, −0.03; 95% CI, −0.05 to −0.001, P  = .02) compared with 25‐gauge microincision vitrectomy surgery in subjects with vitreoretinal disease. However, 27‐gauge microincision vitrectomy surgery subjects had no significant difference in the wound closure time (MD, −8.45; 95% CI, −23.44 to 6.55, P  = .27), operation time (MD, 0.85; 95% CI, −1.17 to 2.86, P  = .41), intraocular pressure at postoperative day 1 (MD, 0.42; 95% CI, −1.45‐2.28, P  = .66), primary anatomical success rate (OR, 0.83; 95% CI, 0.42‐1.63, P  = .58), and central macular thickness (MD, 1.81; 95% CI, −21.76 to 25.37, P  = .88) compared to 25‐gauge microincision vitrectomy surgery in subjects with vitreoretinal disease. The 27‐gauge microincision vitrectomy surgery subjects had a significantly lower intraoperative and postoperative wound complication, wound suture number, and best corrected visual acuity, and no significant difference in the wound closure time, operation time, intraocular pressure at postoperative day 1, primary anatomical success rate, and central macular thickness compared to 25‐gauge microincision vitrectomy surgery in subjects with vitreoretinal disease. The analysis of outcomes should be with caution because of the low sample size of 12 out of 15 studies in the meta‐analysis and a low number of studies in certain comparisons.